Revolutionizing halls of justice reimagining judicial spaces through queer architecture - Ayo, Marian Kristel I.; Richelle Rhea R. Baria (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
This study investigates the potential of queering architecture to reimagine the Hall of Justice in the Philippines. Rooted in queer theory, which challenges traditional hierarchies, binaries and norms, the research advocates for spaces that celebrate diversity and disrupt systemic imbalances-- principles often absent in institutional environments. These shortcomings are particularly evident in Caloocan, where dense populations and high crime rates are met with judicial branches operating in substandard conditions, reflecting broader inefficiencies and infrastructural inadequacies. The research framework focuses on three critical dimensions: user experience, institutional resistance, and community participation, offering a holistic approach to queering judiciary spaces. This study draws a Cabalfin's (200) concept of mala-baklang espasyo--spaces that embody queerness not merely through use but through fluid, layered expressions of identity--and Branco's (2015) framework of recognition, functionality and access. The proposed design responds to systemic issues in the judiciary by creating inclusive, adaptive, and dignified spaces such as gender-neutral restrooms, humane holding areas, and civic-oriented features like mediation rooms and public parks. By integrating queer architectural thinking into judicial space, the project underscores the value of intersectionality, transparency, and adaptability -- demonstrating that justice can be spatially inclusive. This approach offers a foundation for further studies exploring the intersectionality of queerness in architecture and its potential to reshape public institutions.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Queer theory; Sexual minorities; Homosexuality and architecture